2017
DOI: 10.1038/srep40424
|View full text |Cite
|
Sign up to set email alerts
|

Shigatoxin encoding Bacteriophage ϕ24B modulates bacterial metabolism to raise antimicrobial tolerance

Abstract: How temperate bacteriophages play a role in microbial infection and disease progression is not fully understood. They do this in part by carrying genes that promote positive evolutionary selection for the lysogen. Using Biolog phenotype microarrays and comparative metabolite profiling we demonstrate the impact of the well-characterised Shiga toxin-prophage φ24 B on its Escherichia coli host MC1061. As a lysogen, the prophage alters the bacterial physiology by increasing the rates of respiration and cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…aeruginosa. This was previously described for phages transferring genes horizontally in Escherichia coli (40). Here, we showed that phages 24 (CF) and 200 (BR) when integrated into PAO1 as lysogens have the greatest impact reducing the susceptibility to the antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa. This was previously described for phages transferring genes horizontally in Escherichia coli (40). Here, we showed that phages 24 (CF) and 200 (BR) when integrated into PAO1 as lysogens have the greatest impact reducing the susceptibility to the antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%
“…Stx phages play key roles in STEC virulence because they not only carry Shiga toxin-encoding genes but also control their expression. However, little is known about the function of other phage-encoded proteins and how they impact on the host [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…E. coli lacking cryptic prophages display decreased resistance to environmental stresses such as osmotic, oxidative, and acid stress, as well as antimicrobial agents (Wang et al, 2010). Lysogenisation of E. coli K-12 by F24 B , one of the Stx2 phages, modulates bacterial metabolism and raises antimicrobial tolerance (Holt et al, 2017). Therefore, phage lysogenisation enhances the survival of the host bacterium in adverse environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The number of phage particles in environmental samples is estimated to be 10-fold higher than results suggest that prophages alter the gene expression pattern of the host. The impact of Stx2 phage integration on gene expression in E. coli K-12 has been investigated (Holt et al, 2017;Su et al, 2010;Xu et al, 2012). However, the influence of environmental factors on Stx2 phagedriven changes in E. coli has not been clarified.…”
mentioning
confidence: 99%